1975
DOI: 10.1139/z75-217
|View full text |Cite
|
Sign up to set email alerts
|

Paratylenchus neoprojectus n. sp. (Paratylenchinae: Nematoda) from alfalfa fields in Alberta, Canada

Abstract: Paratylenchus neoprojectus n. sp. was found with P. projectus in soil around alfalfa collected from Breton, Alberta. The diagnostic characters established for P. neoprojectus were determined by studies of a population reared from a single larva. It has a spear 28 to 31 μ long. Lip region round, in some cases faintly truncate. Excretory pore usually is at the level of the basal esophageal bulb, 72 to 88 μ from the anterior end. Ovary prominently developed. Tail generally conically rounded, in some cases broadly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The newly obtained sequences of the D2-D3 expansion segments of the 28S rRNA, the ITS of the rRNA, and partial COI mtDNA genes were aligned using ClustalX 1.83 [91] with corresponding published gene sequences [13,14,23,24,26,30,[65][66][67]69,71,80,[92][93][94][95][96][97]. Outgroup taxa for each dataset were chosen based on previously published data [30].…”
Section: Phylogenetic and Sequence Analysismentioning
confidence: 99%
“…The newly obtained sequences of the D2-D3 expansion segments of the 28S rRNA, the ITS of the rRNA, and partial COI mtDNA genes were aligned using ClustalX 1.83 [91] with corresponding published gene sequences [13,14,23,24,26,30,[65][66][67]69,71,80,[92][93][94][95][96][97]. Outgroup taxa for each dataset were chosen based on previously published data [30].…”
Section: Phylogenetic and Sequence Analysismentioning
confidence: 99%
“…As several short stylet pin nematodes species are considered to be plant-pathogenic [22], we performed morphological/morphometrical and molecular studies on these Paratylenchus populations and identified them as P. neoprojectus Wu and Hawn [26], P. tateae Wu and Townshend [27], and a new Paratylenchus sp. that we named P. enigmaticus sp.…”
Section: Of 25mentioning
confidence: 99%
“…The results of this study will aid in distinguishing pathogenic forms from non-pathogenic species, and our findings will be useful in future field experiments to determine the impact of these PPN on potato production. (Figures 1 and 2; Table 1) [26]. Body slender, ventrally arcuate with a bend in the middle of the body when heat relaxed; cuticle finely annulated; lateral field equidistant with four distinct lines; lip region rounded narrow, with anterior end flattened, continuous with the rest of the body; labial framework sclerotization weak; pharyngeal region typical paratylenchoid type; stylet rigid, straight; rounded stylet knobs; dorsal pharyngeal gland opening 5.0-6.0 µm behind stylet knobs; median pharyngeal bulb large elongate, bearing distinct large valves; isthmus short slender, surrounded by nerve ring; basal bulb pyriform, pharyngeal-intestinal valve bilobed; excretory pore situated at the level or middle of pharyngeal basal bulb.…”
Section: Of 25mentioning
confidence: 99%
See 1 more Smart Citation